(3GdMfajI Ydi GdQSGdI GdYVOjIs - (3GdSYjOj, GdCQOHjdj, CHh GdaJM, eMeO Hf Cejf, cGf MjG bHd (B875 (3g`s
(3ChdgG (B:s
(3dc GdMeO LYd Gddg JYGdi eNGWHG JfHjgG Ydi GdbQH hdCf GddGFb HMGd GdMGeO Cf jdGMX GdeMehO ChdG MGVQG hTGgOG Ke jMeOg hGSJHGf efg hLg JbOje bhdg dc Ydi GdMeO hEf cGf GdebGe dchfg ebGes
(3BNQgG (B:s
(3hCcd Odjd fbdj XfjG hcdJG GdebOeJjf ZjQ hGbYI hCjVG GddRhe eYJHQ aj eWdb GdOdjd GdeJfGhd dgeG acja jchf GdYbdj edRheG hGdfbdj ZjQ edRhe hHGdLedI GdaQb djS Ydi eG jfHZj hdfNJe GdcdGe Ydi gPG GdbOQs
(3JHUQI GdYfhGf (B:s
(3fSHJ NWC Ydi WQI GdeNWhW Edi Edi ejQ eMeO GdMfaj GdJHQjRjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/142s
(3cTa GdXfhf (B1/41s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs